Acidification effects in the behavioural responses of temperate reef fish larvae - Castro, Joana Maria Pereira de Paula e, 1987- (2014)
Tese de mestrado. Biologia (Ecologia Marinha). Universidade de Lisboa, Faculdade de Ciências, 2014